Shift work and health of nurses branch of anesthesiology and intensive care - Grabowska-Gaweł, Anna; Ulenberg, Grzegorz; Ulenberg, Agata (Journal of Education, Health and Sport, 2018)
Admission: Shift work and the associated inversion biological rhythms leads over time to a number of changes in the functioning of the body. Some are compensation after a rest and do not constitute a direct threat to health, while others eventually lead to irreversible psychosomatic.Objective of the work: Identify factors resulting from shift work and their impact on health, and psychosomatic individual spheres of nursing department of anaesthesiology and intensive therapy ii individual spheres of life.research Methodology: The study was conducted in 60 nurses using a survey questionnaire containing sociodemographic data and issues covering the most troublesome factors in shift work, the negative impact on their mental and somatic sphere, used forms of relaxation and the impact on individual spheres of life. In order to determine the hierarchy of the factors affecting the individual spheres of applied five-scale assume "0" for no effect, "1" little effect "2" moderate effect, "3" high impact "4" a very large impact.Results: The largest group (51.7%) were women between 31 and 40 years of age (Avg. 35.0 + - 3.7 years), married (76.9%), having children (72.3%). The largest (46.8%) group is working on his post for less than 10 years. For 72% of the most troublesome is night work, work days generally free from work (38%), differentiation of responsibilities per shift (32%). The most frequent symptoms of psychiatric is chronic fatigue (55%), irritability (40%), and somnolence (45%). Somatic reported 94%, these being mainly back pain and lower extremities, appetite disorders and gastrointestinal disorders. In the opinion of 67% of shift work greatly reduces the duties of parental partnerships (68%) and household chores (67%).Conclusions: 1. Shift work in most subjects affects the health psychosomatic revealing back pain, lower limbs, gastric disorders and eating disorders, and chronic fatigue, irritability and sleepiness. 2. Shift work significantly reduces the execution of parental duties, partnerships and household activities. 3. psychiatric deficits are the least felt by women aged 41 - 50 years of working in shifts 16 - 20 years old and more, which may result from reductions in duties related to raising children. 4. Only 2% of the respondents used the active form of relaxation, and reaches 56% of the drugs.